Hepatoprotective effects of methanol extract of Bauhinia purpurea leaves - Yahya, Farhana; Mamat, Siti Syariah; Kamarolzaman, Mohammad Fauzi Fahmi; Sayeden, Altefeh Alsadat; Jakius, Krystal Fredoline; Mahmood, Nur Diyana; Shahril, Mohamad Syahmi; Darnis, Deny Susanti; Zakaria, Zainul Amiruddin (2012)
The objective of the present study was to determine the hepatoprotective activity of methanol extract of Bauhinia purpurea L. leaves (MEBP ; family Fabaceae) using paracetamol and carbon tetrachloride induced liver toxicity models. The dried, ground leaves of B.purpurea (40g) were soaked with 800ml methanol (1:20 (w/v)) for 72h at room temperature, filtered and subjected to the rotary evaporation process. This processes were repeated three times. The vehicle (10% DMSO), 200mg/kg silymarin or MEBP (50, 250 and 500 mg/kg) were administered orally once daily for 7 consecutive days in rats (n=6). Hepatotoxicity was induced by administration of CC14- (0.15 ml/kg) or PCM (3g/kg) 3 hours after the last extract administration. On the 9th day, the animals were sacrificed and the liver was collected for histopathological examination. From the histological observation, hepatic steatosis, lymphocyte infiltration and marked necrosis was observed in CC14 and PCM-treated groups (negative control). Hepatotoxic with PCM pretreated with silymarin or 500 mg/kg MEBP exhibited significant (P<0.05) decreased in he mean of histological scoring compared to the negative control. On the other hand, only 500 mg/kg MEBP significantly (P<0.05) decreased the mean of scoring for CC14-induced hepatotoxicity study compared to the negative control group (P<0.05). In conclusion, the methanol extract of leaves of Bauhinia purpurea exerts potential hepatoprotective property that warrants further investigation.